Glycyrrhiza glabra hydroethanolic extract and manuka honey alone and in combination inhibit bacterial and fungal planktonic cells and biofilms - Gomes, Fernanda (2024)
The natural tendency of polymicrobial infections and co-habitation of bacteria and Candida are currently well-recognized and reported as highly fatal. This kind of interaction is usually associated with drug tolerance, infection relapse, persistence and high mortality. The interest in natural products has emerged and their potential applicability as therapeutic strategies is being constantly explored. Purpose: The main goal of this work is to evaluate the effect of the hydroethanolic extract of Glycyrrhiza glabra, and Manuka honey, in Staphylococcus aureus and Candida tropicalis planktonic cells and single and mixed biofilms. Methods: The effect of both the G. glabra extract and the honey was evaluated by determination of the minimum inhibitory/bactericidal/fungicidal concentrations and by determination of their antibiofilm activity (alone and in combination) on single and mixed-species biofilms. In addition, phenolic compounds were characterized in the hydroethanolic extract with high performance liquid chromatography and mass spectrometry. Results: Among the phenolic compounds identified in the G. glabra extract, flavonoids were the most abundant (≈75 % of the total phenolic compounds), with liquiritigenin being the most representative. S. aureus and C. tropicalis were susceptible to both antimicrobials acting alone. When tested in combination, a significative synergism was observed against C. tropicalis single biofilm formation. Instead, the combination showed an additive effect against mixed biofilms of S. aureus and C. tropicalis. In general the combination G. glabra+honey showed a broader antibiofilm effect than each partner alone. Conclusion: The results showed the good anti S. aureus and C. tropicalis effect of G. glabra and manuka honey against both pathogens tested and highlighted their potential use in combination as therapeutic strategy to combat S. aureus, C. tropicalis and mixed species infections particularly when growing as biofilms.